Oxytocin Massage Training to Increase Exclusive Breastfeeding Coverage - Asnaniar, Wa Ode Sri; Jama, Fatma (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2020)
Breast milk is the best food for babies in their early life. Breast milk is proven to have advantages that cannot be replaced by any food and drink because breast milk contains the most appropriate, complete nutrients and always adjusts to the needs of the baby at any time. The breastfeeding process should ideally be done as soon as the baby is born. Exclusive breastfeeding is given to babies for 6 months without additional food. Based on a survey conducted in the Postpartum Room (Nuri Room) of Bhayangkara Hospital, breastfeeding mothers are motivated to provide exclusive breastfeeding to their children and it was found that 5 out of 7 mothers did not know how to increase breast milk production so their children were previously given formula milk when the mother's breast milk did not come out, were given formula milk when the mother's milk was not flowing. Activities carried out to overcome the problem in the form of Oxytocin Massage Training. The method used was lecture, discussion, demonstration, simulation, and role play. The results obtained were increased knowledge of breastfeeding mothers and families about Oxytocin Massage which can function to increase breast milk production.